Establishing the link between market orientation and agricultural commercialization: empirical evidence from Northern Ghana - Martey, E.; Etwire, Prince M.; Wiredu, A.N.; Ahiabor, B.D.K. (Springer, 2017)
This paper established a positive relationship between market orientation and intensity of commercialization among rural farm households in northern Ghana. The IV Tobit regression estimate suggests that intensity of maize commercialization is significantly determined by education, agro-ecology, household size, total livestock units, farm size, access to formal markets and market orientation. In addition, a highly and unbiased significant positive effect is observed between market orientation and intensity of maize commercialization after controlling for endogeneity in market orientation. Intensity of maize commercialization increased by 0.86% for a 0.1 unit increase in the market orientation index. The empirical implications of the results are discussed.